(untitled) (Journal of Tikapur Multiple Campus, 2017)
The present study on awareness and utilization of reproductive rights among laborer women in Tikapur Municipality. Reproductive rights are the rights of individuals to decide whether to reproduce and have reproductive health. It includes an individual’s right to plan a family, terminate a pregnancy, use contraceptives, learn about sex education in public school and gain access to reproductive health services. The main objectives of this study was to find about the knowledge and utilization of reproductive rights among laborer women. Descriptive study was conducted among 51 laborer women by using non probability purposive sampling method and interview school was used to collect data from eligible laborer women in specially house contraction place. Among 51 respondents most of them (31%) were from age group, (20-24 years) least (7.8%) from early reproductive age group mean age of respondents is (=29 years). Respondents in the study area were from different ethnicity. Cast and religion.Nearly 59%. Responsedents can read and write. Among literate respondents majority (90%) were aware about reproductive health. Among aware respondents all most all were aware about the areas of family planning. About 90% respondents had listend about women empowering programmed among them only few (8%) participation in this programme. Majority of the respondents were visited of ANC and PNC. The conclusion of this study majority of the respondents were aware about reproductive health. At the end comparative studies between educated and no educated is large scale are necessary for generalization of the study result.